2015
DOI: 10.4103/1735-9066.161007
|View full text |Cite
|
Sign up to set email alerts
|

The effects of discharge training and counseling on post-discharge problems in patients undergoing coronary artery bypass graft surgery

Abstract: Background:Advances in coronary artery surgery have reduced morbidity, mortality, and rates of graft occlusion. Discharge programs are important services for the continuity of treatment and must encompass physical, psychological, and social aspects of individual patient care. This study aimed at investigating the effect of planned discharge training and counseling on the problems experienced by patients undergoing coronary artery bypass graft (CABG) surgery.Materials and Methods:A semi-experimental study was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Since educational programs and consultancy services can positively influence the patients’ performance and reduce their postoperative problems, the educational programs and patients’ counseling regarding self-care must be carried out and pursued at home ( 18 ). In a study by Tuna et al ( 18 ), and Akbari and Celik ( 2 ), the findings indicated the positive effect of education and consultancy services offered to the patients on enhancing their performance and decreasing their problems after discharge. The self-care-related problems already experienced by the patients emphasize the need for employment of behavior-change theories in the field since such theories can explore the factors affecting self-care, find their relationship with self-care behaviors, and explore the details, conditions, method, and timings related to these relationships ( 19 ).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Since educational programs and consultancy services can positively influence the patients’ performance and reduce their postoperative problems, the educational programs and patients’ counseling regarding self-care must be carried out and pursued at home ( 18 ). In a study by Tuna et al ( 18 ), and Akbari and Celik ( 2 ), the findings indicated the positive effect of education and consultancy services offered to the patients on enhancing their performance and decreasing their problems after discharge. The self-care-related problems already experienced by the patients emphasize the need for employment of behavior-change theories in the field since such theories can explore the factors affecting self-care, find their relationship with self-care behaviors, and explore the details, conditions, method, and timings related to these relationships ( 19 ).…”
Section: Introductionmentioning
confidence: 96%
“…The common treatment for coronary artery disease is coronary artery bypass graft ( 1 ), which, as the most common surgery for coronary heart disease in the United States, was performed on more than 300,000 patients in 2001. The initial cost of this surgery is estimated to be $30,000 for every patient ( 2 ). Coronary artery operations constitute 60% of the total 50,000 heart surgeries performed in Iran according to the Association of Iranian Heart Surgeons ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is in accordance with a study conducted by Varaei et al (2017), which claimed that educational intervention is effective in promoting cardiac self-efficacy in patients who are candidates for CABG surgery. In a study conducted by Akbari and Çelik (2015), they applied discharge training and counselling on the problems experienced by patients undergoing CABG surgery and determined that it had a positive impact on decreasing the patients’ problems. Rief et al (2017) found that ‘optimising’ CABG patients’ expectations pre-surgery helps to improve outcomes, in particular disability and quality of life, six months after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have focused on the impact of health education (e.g. self-care, medication adherence and sleep quality) on patients’ post-CABG outcomes 6,7. Additionally, many patients with heart disease who have received CABG have expressed the importance of intensive education regarding post-discharge home-based self-care and management 2,8.…”
mentioning
confidence: 99%